Effect of Work Discipline on Employee Performance Mediated Job Satisfaction at RSIA Melinda - Ari Aprian Ferdiansyah; Nurul Hermina (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
This study aims to determine how the effect of work discipline on the performance of RSIA Melinda employees mediated by job satisfaction. The research method used in this research is descriptive and verification method. The population in this study were employees of RSIA Melinda. The sampling method in this study uses